Food Safety Education for Pregnant and Breastfeeding Mothers, Toddlers, Adolescents, and the Elderly - Muthoharoh, Ainun; Rejeki, Herni; Pambudi, Dwi Bagus; Khuzaiyah, Siti; B., Mahdanya Puteri A. (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2023)
Quality food products, halal, free from microbial and chemical contamination, and containing harmless ingredients are the criteria for food products that are suitable for consumption. Especially the use of food products for pregnant and lactating mothers, toddlers, and the elderly must be products that should not be careless. This food safety information can be obtained through education provided in community service activities. Community service activities are carried out by religious leaders and influential community leaders, namely PKK cadres in Ketitang Lor Village, Bojong District, PKK cadres in Sabarwangi Village, Kajen District, Aisyiyah Regional Leaders (PDA) Pekalongan Regency, Nasyiatul Aisyiyah Regional Leaders (PDNA) Pekalongan Regency. This activity is expected to provide an overview and knowledge about the safety of food products for pregnant and lactating mothers, toddlers, children, adolescents and the elderly. The implementation method used is to conduct Communication, Information, and Education (KIE) counseling with the lecture method and discussion. Assessment of knowledge improvement by giving pretest and posttest questionnaires. This activity provides an overview for participants to be able to inform pregnant, lactating mothers, foster parents of infants and adolescents, and the elderly to consume safe and healthy food. Participants are interested and cooperative in participating in the activities. The results of the activity showed an increase in knowledge of 3.21%.